Impact of the strategic sourcing process on the supply chain response to the COVID-19 effects. Issue 6 (20th August 2021) - Frederico, Guilherme F.; Kumar, Vikas; Garza-Reyes, Jose Arturo
Abstract : Purpose: This research investigates the impact of the strategic sourcing process on the supply chain response to COVID-19. The paper presents practitioners' perspectives (experts in supply chain management, especially involved in the procurement field) on the strategic sourcing process's impact on the supply chain response. Design/methodology/approach: The study follows a survey-based approach for data collection. It uses a descriptive survey methodology where questions related to the impact of the strategic sourcing process on the supply chain response in the face of the coronavirus pandemic were explored by practitioners. Findings: In total, 130 valid responses were obtained. The results showed that the majority of respondents agreed or strongly agreed that strategic sourcing positively impacts the supply chain response amid the COVID-19 effects. Also, for the five phases of the strategic sourcing process, the majority of respondents considered them as a high and very high impact on the supply chain response. Research limitations/implications: This paper provides timely insights for practitioners and academics, especially those involved in the supply chain management area, showing how the strategic sourcing process plays an important role in making supply chains more responsive amid disruption situations. Practical implications: Findings of this paper clearly shows the impact of the phases of the strategic sourcing process on the responsiveness of the supply chains amid the COVID-19 pandemic. This can encourage supply chain leadership to devote more time to strategic sourcing initiatives to generate improvements on the supply chain performance. Originality/value: This paper is unique since it brings an unexplored relation in respect to strategic sourcing amid disruption situations, such as the COVID-19 pandemic, from a practitioner's perspective. It also significantly contributes to developing new directions for the supply chain management domain to deal with large-scale disruptions, such as the coronavirus pandemic.